Clostridium tertium: An Unusual Cause of Pyogenic Liver Abscess - Barakat, Mohamed (ACG Case Rep J, 2018)
Pyogenic liver abscess (PLA) is the result of portal vein pyemia, which usually originates from the hepatobiliary system or the gastrointestinal tract. Gram-negative organisms are the most common causative pathogens in PLA. Clostridium tertium is an anaerobic gram-positive, low-virulence organism that most commonly affects neutropenic patients with hematological malignancy and has not been reported to cause PLA. We report an unusual presentation of a C. tertium infection as a PLA in a previously healthy, immunocompetent patient with no identifiable source of portal pyemia.